THE ACTIVITIES OF THE UN COMMITTEE ON THE ELIMINATION OF DISCRIMINATION AGAINST WOMEN AND ITS LEGAL FOUNDATIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides an in-depth analysis of the activities and legal foundations of the United Nations Committee on the Elimination of Discrimination Against Women (CEDAW Committee), established under the Convention on the Elimination of All Forms of Discrimination Against Women. The article begins by examining the historical development and adoption of the CEDAW Convention in 1979 and outlines its significance as a key international legal instrument aimed at protecting women’s rights globally. The functions and responsibilities of the CEDAW Committee are scrutinized, including its monitoring mechanisms, the reporting process for State parties, the issuance of general recommendations, and the handling of individual complaints under the Optional Protocol. Furthermore, the article explores the legal and institutional frameworks that empower the Committee’s operations, particularly the role of international human rights law, UN Charter obligations, and treaty body jurisprudence. Special attention is given to how the Committee contributes to shaping national legal reforms, influencing judicial practices, and advancing gender equality norms in diverse legal systems. Case studies from selected countries are presented to illustrate the Committee's practical impact on state accountability and legislative changes. Additionally, the article evaluates the challenges the Committee faces, such as political resistance, underreporting, and the lack of enforcement mechanisms, and proposes strategies to strengthen its effectiveness. Through a combination of doctrinal legal analysis and empirical case reviews, the article provides a comprehensive understanding of the CEDAW Committee’s pivotal role in the international human rights regime and its ongoing contribution to the elimination of all forms of discrimination against women.